Determinants of shock-coping mechanisms adoption and rural household consumption in Rwanda: A two-stage analysis considering both idiosyncratic and covariate shocks - Fabrice Nkurunziza; Richard Kabanda; Patrick E. McSharry (Cogent Economics & Finance, 2023)
This study investigates the features that contribute to shock-coping mechanisms in rural households in Rwanda, making a significant contribution by considering both idiosyncratic and covariate shocks. We employ a combination of multinomial logit regression (MLR) and two-level hierarchical linear modeling (2-HLM). The study focused on two main characteristics: household characteristics like employment and asset ownership, and shock-coping mechanisms. 4782 Rwandan rural households that experienced shocks were analyzed, exploring variations in factors by consumption level (low, medium, high). The findings of the study revealed that: (1) shock-coping mechanisms are driven by several factors like household characteristics, particularly household composition and employment status, as well as shocks related to covariate shocks, and (2) women spend noticeably less on food, non-food items, and overall expenses than those headed by men when they face covariate shocks. The study suggests that increasing more members employed in non-agricultural businesses and raising livestock, particularly goats could be a pro-low-consumption household strategy in response to shocks. Overall, the study's findings provide valuable insights into the factors that contribute to effective shock-coping mechanisms in rural households and highlight the importance of considering household consumption levels when designing policy interventions.
Keywords: 330; household consumption; Rwanda; shock-coping mechanisms